−x2+x=−10%0D%0A−%0D%0A%0D%0A2%0D%0A+%0D%0A%0D%0A=%0D%0A−%0D%0A10

1 answer

To solve the equation −x^2 + x = −10, we can re-arrange it to form a quadratic equation in standard form by moving all terms to one side:

−x^2 + x + 10 = 0

To solve this quadratic equation, we can use the quadratic formula:

x = (-b ± √(b^2 - 4ac)) / (2a)

In this case, a = -1, b = 1, and c = 10. Plugging these values into the formula:

x = (-(1) ± √((1)^2 - 4(-1)(10))) / (2(-1))
x = (-1 ± √(1 + 40)) / (-2)
x = (-1 ± √41) / (-2)

Therefore, the two solutions to the equation −x^2 + x = −10 are:

x = (-1 + √41) / (-2)
x = (-1 - √41) / (-2)

-------------------------------------------------------------------

Regarding the equation: − 2 + = − 10, it appears to be incomplete and doesn't include any variable or expression to solve for. If you meant to write a different equation, please provide the correct information.